Towards improved participatory scenario methodologies in the Arctic. (3rd April 2021) - Nilsson, Annika E.; Carson, Marcus; Cost, Douglas S.; Forbes, Bruce C.; Haavisto, Riina; Karlsdottir, Anna; Larsen, Joan Nymand; Paasche, Øyvind; Sarkki, Simo; Larsen, Sanne Vammen; Pelyasov, Alexander
ABSTRACT: Participatory scenario methodologies are increasingly used for studying possible future developments in the Arctic. They have the potential to contribute to several high-priority tasks for Arctic research, such as integration of indigenous and local knowledge in futures studies, providing a platform for activating Arctic youth in shaping their futures, identifying Arctic-relevant indicators for sustainable development, and supporting decision-making towards sustainable futures. Yet, to achieve this potential, several methodological challenges need to be addressed. These include attention to whose voices are amplified or silenced in participatory research practices, with special attention to diversification and the engagement of youth. Given the historic and potential future role of disruptive events for Arctic development trajectories, methods are needed in participatory scenario exercises to include attention to the dynamics and consequences of such events and regime shifts. Participatory scenarios can also be further improved through approaches that effectively combine qualitative and quantitative information. Finally, there is a need for systematic studies of how the results of scenario exercises influence decision-making processes. This article elaborates on ways in which attention to these aspects can help make scenarios more robust for assessing a diversity of potential Arctic futures in times of rapid environmental and social change.